Mixed Priapism: An Unusual Case Presentation with Complex Evolution and Literature Review (Revista de Medicina Clinica, 2025)
Introduction: Priapism is a rare urological emergency that may lead to permanent erectile dysfunction if not promptly treated. It is classically divided into ischemic (low-flow) and non-ischemic (high-flow) types. However, the coexistence of both mechanisms—though extremely rare—presents significant diagnostic and therapeutic challenges. Case report: We present the case of a 55-year-old male with a persistent, painful erection lasting 86 hours after recreational use of mephedrone and sildenafil. Initial cavernosal blood gas analysis indicated ischemic priapism, which was unsuccessfully treated with aspiration and irrigation. Subsequent arteriography revealed a cavernous arteriovenous fistula, confirming an additional arterial component. Selective embolization was performed. Due to persistent pain, a penile prosthesis was implanted, which had to be removed following infectious complications and glans necrosis. The patient was discharged after 40 days with significant functional and aesthetic sequelae. Conclusions: This case represents a clinical entity not yet systematically described in the literature: “mixed priapism”, defined by the simultaneous presence of ischemic and non-ischemic mechanisms. A dynamic diagnostic approach and stepwise treatment are emphasized, especially when recreational vasoactive substances are involved.
Keywords: Priapism; Erectile dysfunction; Arteriovenous fistula; Embolization; Mephedrone; Sildenafil